FREE DISPOSAL HULL (FDH), ODER-M AND ODER-ALPHA (α) EFFICIENCY ANALYSIS FOR RUBBER SMALLHOLDERS IN MALAYSIA - Aliyu, A. (International Journal of Research -GRANTHAALAYAH, 2018)
The study examines the technical efficiency of rubber smallholders in Negeri Sembilan under 3 age categories using different method of efficiency analysis which include the Free Disposal Hull (FDH), Expected Oder-m (EOM) and Oder-Alpha (α) (O-α). The analysis was done in such a way that the rubber age was categorized in to All-age, matured-age and Old-age categories. Multistage sampling procedure was used and 307 smallholders were used comprising 307,206 and 101 for all-age, matured-age and old-age categories respectively. The result of the analysis revealed that the mean technical efficiency of all-age, matured-age and old-age crops under FDH were 1.00, 1.00 and 1.00 while that of Order-Alpha and Expected Oder-m were 0.89, 0.89, 0.90 and 0.96, 0.97 0.98 respectively for the all-age, matured-age and old-age crops categories. The percentages of rubber crop farms that are on the FDH production frontier were 100%, 100%, and 100% while under Order Alpha (α) were 13%,10 and 20%. The ones under expected order-m frontier were 29%, 39% and 52% respectively for all-age, matured-age and old-age categories. The mean TE of FDH and mean TE of Order-Alpha were subjected under paired t-test and found to be statistically different from each other. It was revealed that mean TE of FDH was statistically greater than that of Order-M efficiency. Order- M and Order-alpha efficiencies were also subjected under paired mean t-test, and the results indicated that the two means were statistically different from each other. Expected Order-M was found to be statistically higher in magnitude than its counterpart Order Alpha. The study finally concludes that FDH has higher efficiency scores than the other two partial production frontiers. Also deduced from the study was that the old-age category has higher efficiency scores than both the matured-age and all-age categories under both the EOM and Oder Alpha production frontier techniques.. So conclusively the old-age is higher than the matured-age which in turn higher than the all-age category in both the Expected Oder-m and Oder-Alpha production frontiers. Most importantly, policy planners should be very cautious on specific techniques. They should as well be knowledgeable and comparatively minded on the results obtained from both the Expected Oder-m and Oder-Alpha production frontiers with regards to the policy selections on the rubber crop.